(untitled) (Swiss Medical Weekly, 2024)
BACKGROUND: Benign tracheal stenosis is relatively rare but remains a significant chronic disease due to its drastic symptoms including dyspnoea and inspiratory stridor, and consequent negative effect on quality of life. Traditionally, the surgical approach by resection of the stenotic tracheal segment has been the therapy of choice. However, endoscopic techniques have arisen and may offer a safe and less invasive alternative. OBJECTIVES: The aim of the retrospective study was to evaluate procedure-related safety and outcome of endoscopic treatment of benign tracheal stenosis at a single centre. METHODS: The study included all patients at our institution who between 2013 and 2022 had received endoscopic treatment of benign tracheal stenosis by rigid tracheoscopy, radial incision by electric papillotomy needle and dilation (endoscopic tracheoplasty) followed by triamcinolone acetonide as a local submucosal injection and additionally, from 2020, budesonide inhalation. RESULTS:A total of 22 patients were treated in a total of 38 interventions, each resulting in immediate improvement of symptoms. There were no peri-interventional complications or mortality. Of the 38 interventions, 11 received no triamcinolone acetonide administration, resulting in a 54.5% recurrence rate after an average of 21.1 (±18.0) months, while 27 had local triamcinolone acetonide, with a 37% recurrence rate. Since 2020, we additionally initiated post-interventional budesonide inhalation as recurrence prophylaxis for newly admitted patients and patients with recurrences(n = 8), of whom only one (12.5%) has to date experienced a recurrence. CONCLUSION: Our results indicate that endoscopic tracheoplasty offers a safe and successful, minimally invasive alternative to open surgery for patients with benign tracheal stenosis. We recommend local administration of triamcinolone into the mucosa as an additional treatment to decrease the risk of recurrence. However, given the uncontrolled study design and low sample size, safety and effectiveness cannot be conclusively demonstrated. Nonetheless, our findings suggest promising avenues for further investigation. Further studies on the additional benefit of inhaled corticosteroids are warranted.